Kajian Konsep Desain Interior pada The Diamond Chapel dan The Ritual Chapel di Bali - Caronelita Kristiani (Intra, 2015)
Bali provides many places called the "Wedding Chapel" with different concept in each of its wedding chapel, there are two chapels which have interesting shape and concepts those are The Diamond Chapel dan the Chapel Rituals. They are the objects of the research. The research aims to discover the embodiment of the interior design and the idea of The Diamond Chapel and The Ritual Chapel. This research is qualitative. Data obtained through field observation study, interviews, literature study, as well as documentation is directly analyzed descriptively. The subject matter of the research is focuses on building chapel, chapel architecture, including building facades such as front, side, and rear facade; main entrance, layout, space organization and circulation. Chapel’s interior consists of room-forming elements such as floor, walls, and ceilings; transitional element such as door; space-filling elements such as tables and chairs; utility systems are lighting and HVAC systems; and decorative elements as various accessories. The results showed that the design concept of The Diamond Chapel is identic with shiny and valuable items, the implementation of diamond. The design concept of Ritual Chapel indicates that the building is identical to the Padang house roof. These two buildings are monumental and becoming icon to the surrounding environment.